Meaning of titles in “Shar Tuuj” - Sengee, Badamtsetseg (Mongolian Language and Literature Studies, 2024)
In the introductory part of the research, a brief description of first names, titles, honorific names, nicknames, and occupational names included in human nomenclature is given. A total of 39 terms of state, religion, and wrestling significance were listed in the main part of the study, and the origin, translation, and vocabulary meaning of each word was explained. State titles include king, khan, queen, chinsan, lord, taish, taibu, taibujin, taih, dayu, ish, wan, khan, günwan, beil, beis, taij, behi, beij, jonon, major, zangi, zaisan, zasag, chоchur, hero, honjin, üizen, zelden, 28 titles, mostly from Chinese and Turkish languages, are marked, and religious titles include Dalai Lama, Bandida, Hamba, Tsorj, Lama, Toin, Hutagt, Güüsh, Gür, Tsorj, and Ubash which are mostly of Tibetan and Sanskrit origin., as well as arslan and zaan are marked as wrestlers. “Шар тууж” дахь цол нэрийн утга Хураангуй: Судалгааны удиртгал хэсэгт хүний нэрийн зүйд багтах их нэр, цол нэр, өргөмжлөл нэр, хоч нэр, ажил мэргэжлийн нэр, авгайлга нэрийн тухай товч, ерөнхий өгүүлсэн бол судалгааны гол хэсэг болох цол нэрд төр, шашин, бөхийн холбогдолтой нийт 39 зүйл нэр томьёог ангилан жагсааж, тус бүрд үгийн гарал үүсэл, орчуулга, үгийн сангийн утгыг тайлбарлав. Төрийн цол нэрд хаан, хан, хатан, чинсан, ноён, тайш, тайбу, тайбужин, тайх, даюү, иш, ван, гүн, гүнван, бэйл, бэйс, тайж, бэхи, бэйж, жонон, хошууч, занги, зайсан, засаг, чөөхүр, баатар, хонжин, үйзэн, зэлдэн зэрэг голдуу хятад, түрэг хэлнээс гаралтай 28 зүйлийн цол нэр тэмдэглэгдсэн бол шашны цол нэрд далай лам, бандида, хамба, цорж, лам, тойн, хутагт, гүүш, гүр, цорж, убаш зэрэг голдуу Төвөд, Санскрит гаралтай 9 зүйл цол, мөн арслан, заан гэх 2 зүйл бөхийн цол тэмдэглэгдсэн байна. Түлхүүр үг: Шар тууж, хүний нэр, цол нэр, төрийн цол нэр, шашны цол нэр, бөхийн цол нэр